Improving Dental Public Health Services through Advancement of a Workforce Agenda - Robert J. Weyant, DMD, DrPH (Blackwell Synergy, 2006)
The dental public health workforce in the United States presently is inadequate to meet the needs of the nation, and the situation is getting worse.